FORMULATION AND PHYSICAL CHARACTERIZATION OF BLACK SOYBEAN (Glycine Max L.) VARIETY OF DETAM II TABLETS WITH DRY GRANULATION METHOD - Amelia, Ria (International Journal of Natural Science and Engineering, 2021)
Black Soybeans (Glycine max L.)  Detam II varieties  have a higher protein content than other varieties. The high protein content in soybeans (Glycine max L.) is directly proportional to the levels of flavonoid compounds. Flavonoid compounds have been known to have potential as antioxidant compounds that can be beneficial for health. This study aims to obtain a tablet formulation of black soybean (Glycine max L.) detam II varieties . The research was conducted from February to October 2020 at the Pharmaceutical Technology Laboratory STIKes Mitra Keluarga. Preparation of black soybean (Glycine max L.) tablet of detam II variety by slugging method. Detam II black soybean tablets (Glycine max L.) were made into 5 formulas with 250 mg black soybean powder (Glycine max L.) content of detam II varieties in each formula. the differentiated variable is the tablet excipient compound in each formula. Evaluation of black soybean (Glycine max L.) tablet granules of detam II variety by testing water content,compressibility, flow time, angle of rest and tablet evaluation by testing organoleptic, weight, hardness, brittleness and disintegration time. The results showed that a formula  3, 4 and 5 are the recommended formulations for the manufacture of black soybean tablets (Glycine max L.) detam II varieties even though all formula ( F1-F5)  were below the friability value requirements due to several factors. Gelatin excipient and PVP K30 for the manufacture of black soybean tablets (Glycine max L.) detam II varieties are the best choices as tablet fillers.